Pengelolaan Pembelajaran pada Pelatihan Pengelola Pelatihan Pertanian dan Perdesaan Swadaya - Indah Rahmawati; Edi Widianto; M. Ishaq (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
Increasing competence in non-formal education requires effective management including planning, implementation, and evaluation. Whereas to get decent job opportunities, non-formal education services are needed that can improve work competences. This study aims to describe online learning management in pusat pelatihan pertanian dan perdesaan swadaya (P4S) managers training at balai besar pelatihan pertanian (BBPP) Ketindan in terms of planning, implementation, and evaluation aspects. This research uses a qualitative approach. Data was collected using observation, interview and documentation techniques which were then analyzed using Miles and Hubberman qualitative data analysis. Checking the validity of the data in this study was carried out by using triangulation techniques. The results of the study show that online learning management in P4S institutional management training includes: (a) the training planning process is prepared by the program and cooperation section which begins with identifying training needs in the field, preparing training titles then determining training targets and budgeting training costs in accordance with the activity plans are prepared, (b) the implementation of training activities is carried out using the Adult Education/Andragogy approach and is carried out online by utilizing the Learning Management System (LMS) through the BBPP Ketindan e-learning site, the training implementation process is managed by the non-apparatus training section , (c) evaluation activities include initial evaluation activities or pre-test which aims to determine the extent of participants' knowledge before participating in training activities, and final evaluation or post-test conducted to determine the extent of improvement in knowledge of the training participants before and after participating in the training activities.